Local Government Reform in South Africa: The Quest for Review and Repositioning of Municipal Administration - Madumo, O.S.; Koma, S.B. (Journal of Reviews on Global Economics, 2019)
The endemic municipal governance problems experienced since the dawn of the democratic dispensation manifested through the constant dysfunctional state of municipalities, poor financial performance and poor political leadership clearly necessitate that the national government should revisit and review the constitutional powers granted to the sphere of local government and contemplate introducing a pragmatic model of running municipal affairs. This paper argues that there is a need to review and reposition the model of local government in order to ensure that municipalities appropriately fulfil their constitutional obligations. The existing research pointed to the relevance of the application and utilisation of the different categories of municipalities, thereby enabling the effective delivery of services to communities. Therefore, the review will amongst others, entail the critical examination of the interventions spearheaded by the national government namely, the Project Consolidate; Municipal Turnaround Strategy/Municipal Infrastructure Support Agent; Operation Clean Audits-2014 and the recently launched Back-to-Basics approach. Based on literature and document reviews this article concludes that the abovementioned interventions have not yielded the desired results yet, if the current performance of municipalities such as Madibeng, Maquasi-Hills, Lekwa-Teemane, Randfontein, Thaba Chweu, Bushbuckridge and Mtubatuba is anything to go by. The outcomes point to the urgent need for a review of the current model of local government that is utilised within a developing society, which is mired with many developmental challenges. This is relevant because South Africa aims at becoming a capable and developmental state as encapsulated in the NDP (National Development Plan) 2030 and for it to achieve such, municipalities are a critical enabler since they operate at the grassroots level.